Analysis of Air Basin State of Industrial-Urban Agglomerations in the North-Western Black Sea - Chugai, Angelina; Safranov, Tamerlan; Holik, Yuriy (International Journal of Engineering and Technology, 2018)
The paper considers the influence of the main sources of technogenic pollution on the state of the atmospheric air of the North-Western Black Sea regions. For the first time, a comprehensive assessment of a level of technogenic load on the air basin from the stationary and mobile sources was made and the impact of the stationary and mobile sources on the overall level of air pollution was determinedÂ Â